2010
DOI: 10.1001/archgenpsychiatry.2010.139
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Cognitive Impairments in Attention-Deficit/Hyperactivity Disorder Into 2 Familial Factors

Abstract: Context Attention deficit hyperactivity disorder (ADHD) is associated with widespread cognitive impairments, but it is not known whether the apparent multiple impairments share etiological roots, or whether separate etiological pathways exist. A better understanding of the etiological pathways is important for the development of targeted interventions and for identification of suitable intermediate phenotypes for molecular genetic investigations. Objective To determine, using a multivariate familial factor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
166
3
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 154 publications
(196 citation statements)
references
References 65 publications
24
166
3
3
Order By: Relevance
“…This might be reflected in the developmental hypothesis by Halperin and colleagues (Halperin and Schulz 2006;Halperin et al 2008) who postulate the role of both early enduring neurobiological processes involved in the aetiology of ADHD, and later developing moderating neurobiological processes involved in the persistence or desistance of ADHD during adolescence. It may also be reflected in the identification of two distinct familial cognitive factors, which largely account for familial (thought to be genetic) influences on ADHD, and which may map onto the neurocognitive processes proposed by Halperin and colleagues (Kunsti et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This might be reflected in the developmental hypothesis by Halperin and colleagues (Halperin and Schulz 2006;Halperin et al 2008) who postulate the role of both early enduring neurobiological processes involved in the aetiology of ADHD, and later developing moderating neurobiological processes involved in the persistence or desistance of ADHD during adolescence. It may also be reflected in the identification of two distinct familial cognitive factors, which largely account for familial (thought to be genetic) influences on ADHD, and which may map onto the neurocognitive processes proposed by Halperin and colleagues (Kunsti et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous research has suggested aetiological separation between omission errors and reaction time variability (Kuntsi et al, 2010). In this study, we see significant covariation suggesting a shared underlying mechanism in relation to treatment response for these two different aspects of attention (r = 0.63, p < .001).…”
Section: Discussionmentioning
confidence: 99%
“…This data was supported by a recent large study that obtained evidence that the same two processes account for eighty five percent and twelve percent respectively of the genetic influence of ADHD. 47 There are several genes implicated in the pathogenesis of ADHD. Genetic variants among the dopamine receptor genes D4 (DRD4) and D5 (DRD5) provide the most consistent findings supported by a large meta-analysis.…”
Section: Pathophysiology Clinical Features and Treatment Optionsmentioning
confidence: 99%